New Pathologic Stratification of Microvascular Invasion in Hepatocellular Carcinoma: Predicting Prognosis After Living-donor Liver Transplantation. Issue 6 (June 2015) - Iguchi, Tomohiro; Shirabe, Ken; Aishima, Shinichi; Wang, Huanlin; Fujita, Nobuhiro; Ninomiya, Mizuki; Yamashita, Yo-ichi; Ikegami, Toru; Uchiyama, Hideaki; Yoshizumi, Tomoharu; Oda, Yoshinao; Maehara, Yoshihiko
Abstract : Background: Vascular invasion of hepatocellular carcinoma (HCC) has a high incidence of recurrence after liver transplantation. Patients with microvascular invasion (MVI) show a high tumor grade; however, some show a good prognosis. This retrospective study aimed to investigate whether the degree of MVI affects prognosis after living-donor liver transplantation. Methods: A total of 142 patients with HCC who had undergone living-donor liver transplantation were histologically evaluated about the number of invaded vessels and the maximum number of invading carcinoma cells. Patients with MVI were classified into two subgroups: high MVI group (n = 38), which showed more than 50 carcinoma cells in the vessels, with multiple invaded vessels; and low MVI group (n = 17), which showed MVI, but not high MVI. Results: Analysis of recurrence-free survival showed that high MVI group had significantly poorer outcomes than the other groups ( P < 0.001). High MVI group had significantly higher α-fetoprotein levels, des-γ-carboxy prothrombin levels, number of tumors, a larger tumor size, and a higher percentage of poorly differentiated HCC than non-MVI group. High MVI was an independent prognostic factor for recurrence-free survival ( P = 0.030). Among patients exceeding the Milan criteria (n = 61), high MVI group had significantly poorer outcomes than the other groups for recurrence-free survival ( P = 0.003). Patients in high MVI group had significantly higher des-γ-carboxy prothrombin levels and a larger tumor size than non-MVI group. High MVI was an independent prognostic factor for recurrence-free survival ( P = 0.014). Conclusion: In living-donor liver transplantation for HCC, high MVI is a novel pathologic marker for predicting prognosis. Abstract : This study investigates the degree of microvascular invasion by hepatocellular carcinoma at the time of living donor liver transplantation. The results show that a high microvascular invasion of more than 50 carcinoma cells in vessels is an independent prognostic factor for recurrence-free survival.